Big Surprise in the Bug Tank - Horowitz, Ruth; Holub, Joan (New York : Dial Books for Young Readers, 2005)
Two brothers get two giant hissing cockroaches as pets and then must figure out a way to deal with the resulting population explosion.
Keywords: Brothers -- Fiction; Cockroaches -- Fiction; Pets -- Fiction; Fiction